Polska T. - Sobańska, Aleksandra (Wydawnictwo Uniwersytetu Łódzkiego, 2026)
The aim of the book set in the interpretative paradigm is to (1) reconstruct the social world of transgender women; (2) gain in-depth knowledge of the political, institutional, discursive, and individual opportunity structures that condition the process of gender transition in Poland; (3) present the individual experiences of transgender women; and (4) show their strategies of functioning in relation to diverse socio-demographic characteristics. The theoretical framework is grounded in the concepts of social worlds and opportunity structures, while the methodological strategy is based on the biographical method, supported by the triangulation of research techniques: autobiographical narrative interviews, in-depth interviews, qualitative preliminary analysis of journalistic content and unstructured observation. In the content of the entire book, theory is intertwined with the results of empirical research. The social world of transgender women is extremely diverse in terms of the variety of approaches to the gender transition process, the needs associated with it, opinions on authenticity, ways of legitimising transgender issues, etc. Furthermore, there is a complex set of political, institutional, discursive and individual opportunity structures at work in this world, which intertwine and influence each other, shaping the lived experiences of transgender women.